Traditional vs Modern Groceries from Islamic Perspective in Indonesia - Sofyan Bachmid; Mokh Ulil Hidayat; Noval Noval (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Despite extensive research on the competition between modern and traditional retailers, there is a lack of investigation into specific factors that influence consumer choices and directly impact sales revenue. There is a scarcity of research exploring these issues from the perspective of Islamic business. To address this gap, the study aims to examine consumer preferences in purchasing decision at Traditional and Modern groceries. This study employed a quantitative approach by distributing questionnaire to 100 customers in Palu city, Indonesia. Data analysis involved path analysis and bootstrap biased correlation. The findings highlight the significant impact of product variants, pricing strategies, and promotional efforts by modern retailers on sales revenue in traditional retail stores through purchasing decisions. However, shopping convenience did not exhibit a significant influence, indicating the need for improvement. The competition between traditional and modern retail is primarily driven by shifting consumer behavior and relatively weaker marketing strategies employed by traditional retailers. This study suggests that to maintain their market position, traditional retailers should enhance their marketing strategies by expanding product offerings, setting competitive prices, and executing effective promotional campaigns. Prioritizing the improvement of shopping convenience is crucial to meet customer expectations and preferences.